Character Education as a Foundation for Students’ Mental Readiness in Facing the Dynamics of the Modern Industrial World - Siti Nuraida Susanti; Novi Aulia; Dwi Andicky Nopriadytia; Karyanti Karyanti; Asep Solikin; M. Fatchurrahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The increasingly complex development of the industrial world requires university graduates to possess strong mental readiness and well-internalized character. The gap between academic competence and psychological readiness remains a critical issue in higher education. Aim: This study aims to analyze the effect of character education on students’ mental readiness in facing the industrial world when viewed from economic status. Method: This research employed a quantitative approach with a descriptive-correlational design. Data were collected through the distribution of Likert-scale questionnaires to 200 active university students. Data analysis techniques included descriptive statistical analysis and correlation testing. Result and Discussions: The results indicate that the majority of students fall into the high mental readiness category, while levels of character education are predominantly in the moderate to high categories. The discussion of the findings suggests a positive relationship between character education and mental readiness, particularly among students with middle and high economic status. Conclusion: This study concludes that character education plays a significant role in building students’ mental readiness. Recommendations are aimed at strengthening context-based, character-based learning designs and advancing intervention-based research.